Approche lexicographique de réseau : constitution de nomenclature wolof - Abibatou Diagne (Linguistik Online)
Lexicographic work on languages often adopts traditional text-based dictionary approaches. Wolof is no exception. In an explanatory and combinatorial approach, Mel’čuk/Clas/Polguère 1995 have proposed DEC, which is the applied side of Meaning Text Theory (MTT). The project to develop lexical networks (French, Russian, etc.), which aims to structure lexical information in a relational way, falls within this same framework Polguère (2014). The organization of units into a lexical network reveals the nature of the relationships maintained by these units. This study constitutes the first phase in the construction of this lexical network project, which involves proposing a priming nomenclature composed of a set of vocables that will serve as entries for the network. As its name implies, it serves as a starting point for choosing from among the vocables listed on the basis of their high communicative potential and the high density of lexical relations with other units. We set out to provide the principles for choosing vocables and to re-specify certain parts of speech traditionally adopted in grammar, but which do not apply rigorously to Wolof. The last point of the study concerns the possibilities of extending the nomenclature with the LFs used to weave the relationships between units.